MORPHOMETRY OF NECK-SHAFT ANGLE IN DRIED ADULT HUMAN FEMORA OF NORTH INDIAN POPULATION - SINGH, GURPREET; DHINDSA, GURSHARAN SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The present study aimed to record the femoral-neck shaft angle was carried out which would be of help to the orthopedicians while carrying out surgical repairs around the hip joint especially in fracture of the neck of femur. Materials and Methods: A total of 100 North Indian unpaired dry adult human femora (Right-50, Left-50) of unknown sex were studied. Neck-shaft angle (NSA) of the femur was measured with the help of goniometer and measurements were recorded in degrees. The raw data obtained were statistically analyzed. Range, mean, standard deviation, and standard error of mean were determined. Results: The mean NSA was found to be 127.63°+3.48° (Right=127.80°+3.56° and Left=127.46°+3.42°) with a range of 122°–137° (Right=122°–137° and Left=122°–136°). No significant difference in values of neck-shaft angle was found in the right and left femora. Conclusion: The overall goal of this study was to generate information that would be useful for geometric modeling of femora and collecting data which could prove useful for the development of prosthetic implants